The direct production of jet-fuel from non-edible oil in a single-step process. (15th October 2015) - Choi, Il-Ho; Hwang, Kyung-Ran; Han, Jeong-Sik; Lee, Kyong-Hwan; Yun, Ji Sun; Lee, Jin-Suk
Highlights: Single-step reaction for a direct production of jet-fuel from non-edible oil with no added hydrogen. Jet-fuel produced using a Pd/beta zeolite in a single-step reactor contained normal, isomer and aromatic hydrocarbons. Degrees of deoxygenation of wasted soybean oil and palm fatty acid distillates were 95.5% and 94.3%, respectively. Abstract: The catalytic conversion of non-edible oil was carried out over a Pd-based zeolite catalyst in a single-step process (SSP) with no added hydrogen to examine the possibility of the direct production of hydrocarbons in the ranges of jet fuel. The conversion of stearic acid, a model fatty acid compound, reached 100% and the proportion of hydrocarbons in the jet-fuel range was 69.3% over a Pd/beta-zeolite catalyst at 270 °C in a SSP. In addition, the obtained jet-fuel was composed of normal, isomer, and aromatic hydrocarbons, all of which were oxygen-free compounds. Through the catalytic conversion of raw materials, waste soy bean oil (SBO) and palm fatty acid distillate (PFAD), a high-quality jet-fuel product was also obtained in a SSP. The degree of oxygen removal was approximately 95% for the conversions of SBO and PFAD.